Resiliensi Mahasiswa Korban Verbal Bullying Ditinjau Berdasarkan Gender - Maizura, Nining; Indreswari, Henny; Eva, Nur; Muslihati, Muslihati; Lismaini, Lismaini (JURNAL KONSELING GUSJIGANG, 2024)
Verbal bullying is a form of psychological aggression that often decreases students' resilience, defined as the ability to recover and adapt to stress or trauma. This study aims to explore the resilience levels of students who are victims of verbal bullying at Universitas Negeri Malang, identify the influencing factors, and provide evidence-based intervention recommendations. A quantitative descriptive method was employed, using surveys as the data collection tool. Resilience was measured using the Connor-Davidson Resilience Scale (CD-RISC) with purposively selected respondents. Data analysis through descriptive statistics and mean tests showed no significant differences in resilience based on gender, age, or social support. The results indicate that resilience is influenced by internal factors such as self-esteem and emotional intelligence, as well as external factors such as social support. The study recommends integrating peer counseling based on role modeling and professional counseling to enhance resilience, along with emotional intelligence training, strengthening social support, and fostering a supportive campus environment.